Floor vegetation management affects diversity and composition of mycorrhizal symbionts and soil microbial communities in a Mediterranean olive orchard - Arianna GRASSI; Irene PAGLIARANI; Eleonora GRANATA; Luciano AVIO; Caterina CRISTANI; Flavia MASCAGNI; Manuela GIOVANNETTI; Chiara PICCINI; Claudio CANTINI; Alessandra TURRINI; Monica AGNOLUCCI (Pedosphere, 2026)

Horizontal gene transfer in Saccharomyces cerevisiae and other Saccharomycotina yeasts: a review - Arianna Grassi; Ugo Rogo; Marco Fambrini; Claudio Pugliesi; Monica Agnolucci (World Journal of Microbiology and Biotechnology, 2026)

Chronic Styrene Exposure Causes Oxidative Stress, Neuroinflammation, and Hippocampal Memory Dysfunction via NLRP3 Inflammasome Activation - Raffaele Montuoro; Anna Pisani; Veronica Mohamed Hizam; Claudia Vernamonte; Giammarco Boni; Jacopo Galli; Renata Sisto; Fabiola Paciello; Anna Rita Fetoni; Claudio Grassi (Molecular Neurobiology, 2026)
Several studies focused on the molecular mechanisms linking oxidative stress and inflammation, due to their crucial role in different pathological conditions, including neurodegenerative disorders. Here, we studied the link between redox unbalance and neuroinflammation in a model of styrene-induced toxicity in the hippocampus. We used a rat model of chronic styrene exposure to assess its impact on hippocampal function. Behavioral tests were performed to evaluate recognition and spatial memory. Molecular and histological analyses were carried out to measure ROS production, inflammatory markers (COX-2, TNF-α, IL-1β), and immunoreactivity for IBA-1 and GFAP. Synaptic alterations, activation of pro-apoptotic pathways, and NLRP3 inflammasome levels were also evaluated. We found that toxic exposure to styrene can affect both recognition and spatial memory by causing functional, morphological, and molecular alterations in the hippocampus. Indeed, we observed increased ROS production and elevated levels of inflammatory markers, as well as increased IBA-1 and GFAP immunoreactivity, suggesting an activation of the immune system with the involvement of microglia and astrocytes in the hippocampus of styrene-treated animals. These findings were associated with molecular and structural synaptic alterations and activation of pro-apoptotic pathways. Moreover, we pointed out the possible involvement of inflammasome activation in mediating oxidative-inflammatory damage, and we documented an increased level of NLRP3 inflammasome after styrene exposure. Our data provide novel experimental evidence of styrene-induced memory dysfunctions, demonstrating that exposure to this toxic compound can impinge on the hippocampus through a mechanism involving the ROS-driven inflammation, activating the NLRP3 inflammasome axis. From a translation point of view, our results indicate that styrene exposure can be a high-risk factor for developing cognitive deficits and suggest considering the ROS/NLRP3 pathway as a target to prevent/attenuate neurotoxicity.

High promiscuity among females of the invasive pest species Drosophila suzukii - Simone Puppato; Giulia Fiorenza; Davide Carraretto; Ludvik Marcus Gomulski; Giuliano Gasperi; Carlos Caceres; Alberto Grassi; Maria Vittoria Mancini; Antonio De Cristofaro; Claudio Ioriatti; Robin Guilhot; Anna Rodolfa Malacrida (Molecular Ecology, 2023)
Drosophila suzukii (Matsumura, 1931), the spotted‐wing drosophila, is a highly invasive fruit fly that spread from Southern Asia across most regions of Asia and, in the last 15 years, has invaded Europe and the Americas. It is an economically important pest of small fruits such as berries and stone fruits. Drosophila suzukii speciated by adapting to cooler, mountainous, and forest environments. In temperate regions, it evolved seasonal polyphenism traits which enhanced its survival during stressful winter population bottlenecks. Consequently, in these temperate regions, the populations undergo seasonal reproductive dynamics. Despite its economic importance, no data are available on the behavioural reproductive strategies of this fly. The presence of polyandry, for example, has not been determined despite the important role it might play in the reproductive dynamics of populations. We explored the presence of polyandry in an established population in Trentino, a region in northern Italy. In this area, D. suzukii overcomes the winter bottleneck and undergoes a seasonal reproductive fluctuation. We observed a high remating frequency in females during the late spring demographic explosion that led to the abundant summer population. The presence of a high degree of polyandry and shared paternity associated with the post‐winter population increase raises the question of the possible evolutionary adaptive role of this reproductive behaviour in D. suzukii .

First report on classical biological control releases of the larval parasitoid Ganaspis brasiliensis against Drosophila suzukii in northern Italy - Lorenzo Fellin; Alberto Grassi; Simone Puppato; Alberto Saddi; Gianfranco Anfora; Claudio Ioriatti; Marco Valerio Rossi-Stacconi (BioControl, 2023)
Current management strategy of the invasive fruit fly Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) exploits different tools but relies mainly on chemical control. In the invaded areas, the local natural enemy community mostly consists of generalist pupal parasitoids unable to control the pest efficiently. Conversely, in the pest native area, there are more specialized sympatric larval parasitoids attacking D. suzukii . Following foreign explorations and quarantine risk assessments, the larval endoparasitoid Ganaspis brasiliensis (Ihering) (Hymenoptera: Figitidae) was selected as the best candidate for classical biological control programs. In 2021, the first ever propagative biocontrol program using a Japanese G1 lineage of G. brasiliensis started in Italy. Here we report the results of the first year of releases in the province of Trento (Northeast Italy), wherein G. brasiliensis was released in 12 locations. Pre- and post-release samplings on fresh and fallen fruits were performed around the release points to assess the recapture rate, the impact of the exotic parasitoid on D. suzukii and its potential interactions with local non-target species. After releases, G. brasiliensis was recovered at 50% of the locations. The exotic parasitoid only emerged from D. suzukii , mostly from fresh fruit still on the plant. Post-overwintering monitoring revealed the presence of a four G. brasiliensis individuals at two release locations.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Altered Nup153 Expression Impairs the Function of Cultured Hippocampal Neural Stem Cells Isolated from a Mouse Model of Alzheimer’s Disease - Lucia Leone; Claudia Colussi; Katia Gironi; Valentina Longo; Salvatore Fusco; Domenica Donatella Li Puma; Marcello D’Ascenzo; Claudio Grassi (Molecular Neurobiology, 2019)

Correction to: The Medial Septum Is Insulin Resistant in the AD Presymptomatic Phase: Rescue by Nerve Growth Factor-Driven IRS1 Activation - Valentina Sposato; Nadia Canu; Elena Fico; Salvatore Fusco; Giulia Bolasco; Maria Teresa Ciotti; Matteo Spinelli; Delio Mercanti; Claudio Grassi; Viviana Triaca; Pietro Calissano (Molecular Neurobiology, 2019)

Biliverdin Reductase-A Mediates the Beneficial Effects of Intranasal Insulin in Alzheimer Disease - Eugenio Barone; Antonella Tramutola; Francesca Triani; Silvio Calcagnini; Fabio Di Domenico; Cristian Ripoli; Silvana Gaetani; Claudio Grassi; D Allan Butterfield; Tommaso Cassano; Marzia Perluigi (Molecular Neurobiology, 2019)

Augmentative releases of Trichopria drosophilae for the suppression of early season Drosophila suzukii populations - Marco Valerio Rossi Stacconi; Alberto Grassi; Claudio Ioriatti; Gianfranco Anfora (BioControl, 2019)

The Medial Septum Is Insulin Resistant in the AD Presymptomatic Phase: Rescue by Nerve Growth Factor-Driven IRS1 Activation - Valentina Sposato; Nadia Canu; Elena Fico; Salvatore Fusco; Giulia Bolasco; Maria Teresa Ciotti; Matteo Spinelli; Delio Mercanti; Claudio Grassi; Viviana Triaca; Pietro Calissano (Molecular Neurobiology, 2019)

Not the one, but the only one: about Cannabis cryptic virus in plants showing ‘hemp streak’ disease symptoms - Laura Righetti; Roberta Paris; Claudio Ratti; Matteo Calassanzio; Chiara Onofri; Davide Calzolari; Wulf Menzel; Dennis Knierim; Gianmaria Magagnini; Daniela Pacifico; Gianpaolo Grassi (European Journal of Plant Pathology, 2018)

Drosophila suzukii population response to environment and management strategies - Nik G. Wiman; Daniel T. Dalton; Gianfranco Anfora; Antonio Biondi; Joanna C. Chiu; Kent M. Daane; Beverly Gerdeman; Angela Gottardello; Kelly A. Hamby; Rufus Isaacs; Alberto Grassi; Claudio Ioriatti; et al. (Journal of Pest Science, 2016)

Herpes simplex virus type 1 infection in neurons leads to production and nuclear localization of APP intracellular domain (AICD): implications for Alzheimer’s disease pathogenesis - Livia Civitelli; Maria Elena Marcocci; Ignacio Celestino; Roberto Piacentini; Enrico Garaci; Claudio Grassi; Giovanna De Chiara; Anna Teresa Palamara (Journal of NeuroVirology, 2015)

New perspectives in cyclic nucleotide-mediated functions in the CNS: the emerging role of cyclic nucleotide-gated (CNG) channels - Maria Vittoria Podda; Claudio Grassi (Pflügers Archiv - European Journal of Physiology, 2014)

Epigenetic Modulation of Adult Hippocampal Neurogenesis by Extremely Low-Frequency Electromagnetic Fields - Lucia Leone; Salvatore Fusco; Alessia Mastrodonato; Roberto Piacentini; Saviana Antonella Barbati; Salvatore Zaffina; Giovambattista Pani; Maria Vittoria Podda; Claudio Grassi (Molecular Neurobiology, 2014)

Infectious Agents and Neurodegeneration - Giovanna De Chiara; Maria Elena Marcocci; Rossella Sgarbanti; Livia Civitelli; Cristian Ripoli; Roberto Piacentini; Enrico Garaci; Claudio Grassi; Anna Teresa Palamara (Molecular Neurobiology, 2012)

Early effects of exercise training on $$ \mathop V\limits^ · {\rm O}_2 $$ on- and off-kinetics in 50-year-old subjects - Yoshiyuki Fukuoka; Bruno Grassi; Marco Conti; Daniela Guiducci; Monica Sutti; Claudio Marconi; Paolo Cerretelli (Pflügers Archiv - European Journal of Physiology, 2002)